Dlaczego walczyłem dla Kupidyna, czyli o walce o średniowieczne rymy w polskim przekładzie Carmina Rivipullensia - Woźniak, Maria Judyta (Collectanea Philologica, 2020)
Carmina Rivipullensia is the only existing collection of medieval Latin love lyrical poetry deriving from Spain. It is a unique testimony of skilful and creative use of the Latin poetic tradition on the Iberian Peninsula. Songs have not yet been translated into Polish. The aim of the article is to present a collection which is little-known in Poland along with a proposed translation of one of the poems and a commentary on literary devices applied in the translation as well as dilemmas faced by a contemporary translator.